Сказки из волшебной лампы - Пыльцын Михаил (Серия "Сказки БЭСТ", 2013)
Экземпляры: Ф. 13 (20200225) / Инвентарный номер: 47655 / Цена: 60.00 / Сис.шифр: 82.3(3) / Авт.знак: С 42 / ГРНТИ: 17.82 / ББК: 82.3(3)